Rewriting the narrative of the infertile female body - Minnaar, Tayla (Stellenbosch Theological Journal, 2021)
This article will explore the possible reimagining of the infertile female body through the lens of theology. The rise of feminist movements and socio-political influence has impacted both men and women's identity. Motherhood is still interconnected with the female identity, and this becomes problematic when women experience reproductive loss. Reproductive loss can challenge one's faith and hope. Socially, when it comes to infertility there is still a negative connotation attached to it. This study serves to break the silence on this topic and explore ways to change the narrative surrounding infertility.